Insulin Requirement for Gestational Diabetes Control Is Related to Higher Vitamin D Levels up to 1 Year Postpartum: A Prospective Cohort Study - María Molina-Vega; María José Picón-César; Fuensanta Lima-Rubio; Carolina Gutiérrez-Repiso; Teresa María Linares-Pineda; María Suárez-Arana; Ana María Fernández-Ramos; Francisco J. Tinahones; Sonsoles Morcillo (MDPI AG, 2022)
Vitamin D deficiency is highly prevalent in pregnant women and has been related to a higher risk of gestational diabetes mellitus (GDM). The aim of this study is to analyze vitamin D status evolution in a population of pregnant women with and without GDM. Two-hundred women were included from January 2019 to February 2022 as follows: Control group -CG-, Lifestyle group -LG- (GDM not requiring insulin), and Insulin group -IG- (GDM requiring insulin). Visits were carried out at baseline, antenatal, postpartum, and 1 year after birth. Vitamin D levels, weight, and insulin resistance were measured at every visit. Data about the season, vitamin D supplementation, Mediterranean diet adherence, and physical activity were included. In the three groups, 134 women were included in the CG, 43 in the LG, and 23 in the IG. Vitamin D levels were similar among the groups at baseline, but they were significantly higher in the LG and IG in comparison with the CG at the antenatal visit and significantly higher in the IG vs. CG and LG at the postpartum and 1 year after birth visits. Vitamin D levels were independently related to vitamin D supplementation and the season at baseline, to the season and belonging to the LG or IG at the antenatal visit, and were only independently associated with belonging to the IG at postpartum and 1 year after birth visits. In conclusion, in our population, women with GDM requiring insulin had higher levels of vitamin D in comparison with those not requiring insulin and healthy controls at postpartum and 1 year after pregnancy. Requiring insulin during pregnancy seems to be a factor that independently determines the levels of vitamin D until 1 year after birth. More studies are required to reproduce these data in other populations and to elucidate the mechanisms underlying these findings.